ON THE RHYTHM OF THE TROCHAIC TETRAMETER IN THE XVIII — THE FIRST THIRD OF THE XIX CENTURY AND THE LAW OF REGRESSIVE ACCENT DISSIMILATION - Kayumova, Venera (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
Despite almost 110 years of scientific study of the rhythm of verse, some problems remain unresolved. In particular, this concerns the evolution of the rhythm of the four-foot chorea and the causes of the law of regressive accentuated dissimilation (RAD). Several opinions have been expressed about the reasons for the RAD law. The evolution of the X4 rhythm is considered in the article with more material than previous scientists, and with a breakdown of statistical data by decades, from 1740 to 1830. The article uses three types of data: relative, theoretical frequencies and ratios of real data to theoretical ones. As a comparative material, the use of iambic tetrameter (Я4) in the same periods is given. The evolution of X4 is compared with the evolution of Я4 in terms of such parameters as the dynamics of stress profiles, changes in the frequencies of rhythmic forms and changes in the frequencies of variant forms. As a result of the analysis, the author of the article comes to the conclusion that there is a unidirectional development of the chorea and iambic rhythms, the differences in the use of rhythmic forms are due to the specifics of the meters, which indicates a common global reason for the evolution of disyllabic meters, which may be associated with the development of the Russian language.
Keywords: trochee tetrameter; iambic tetrameter; law of regressive accent dissimilation; stress profile; rhythmic forms; variants of rhythmic forms